2020
DOI: 10.1177/2158244020979175
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organizational Climate on Faculty Burnout at State and Private Universities: A Comparative Analysis

Abstract: Organizational climate, that is, the atmosphere surrounding an organization, unites features with individual, organizational, and environmental characteristics that affect the behaviors of individuals within the organization. Burnout is accepted as a syndrome that often occurs in people who work together with others. Faculty members in universities are potential burnout candidates due to their relationships with many students, employees, and administrators. To reduce burnout of the faculty members, it is cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 80 publications
0
16
0
3
Order By: Relevance
“…According to Furnham and Goodstein (1997) , organizational climate encompasses a variety of dimensions, including role clarity, career development, respect, communication, reward systems, planning and decision-making, innovation, relationships, teamwork and support, service quality, conflict management, commitment and morale, training and learning, and direction. Dinibutun et al. (2020) identified additional dimensions of organizational climate as managerial competence, balanced workload, task clarity, cohesion, ethics, and participation.…”
Section: Introductionmentioning
confidence: 99%
“…According to Furnham and Goodstein (1997) , organizational climate encompasses a variety of dimensions, including role clarity, career development, respect, communication, reward systems, planning and decision-making, innovation, relationships, teamwork and support, service quality, conflict management, commitment and morale, training and learning, and direction. Dinibutun et al. (2020) identified additional dimensions of organizational climate as managerial competence, balanced workload, task clarity, cohesion, ethics, and participation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the study of [104] indicated that the absence of collaboration between the work team is one of the most important causes of the weak organizational climate that affects quality improvement because continuous improvement can only be achieved through a collaboration team. The previous study, for example, [11], [105] contended that climate has a great important role in higher education institutions due to its prominent role in achieving employee satisfaction and development. Therefore, organizations care to study their internal climate and improve them to continuous quality improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies, the data reveals that organizational climate can enhance quality improvement in the higher education sector [9], [10] affirmed that organizational climate is the most important factor which reflects positive outcome in the institution. Additionally, [11] clarified that appropriate organizational climate is becoming a fundamental approach that stimulates to increase the university's performance and improve the quality of education. Also, [12] revealed that organizational climate is the basis for continuous improvements in quality by identifying imbalance and inefficiency in a performance referred to by employees of all levels in the organization through effective communication between them and the administration.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its closeness to employee positive work attitudes such as job satisfaction, dedication, work efficiency, and employee loyalty, organizational climate has garnered substantial attention from previous and present studies (Bahrami et al, 2016;Jyoti, 2013;Langi et al, 2022;Permarupan et al, 2013;Shanker et al, 2017). An array of past and contemporary studies associated the organizational climate with negative out comes such as intention to leave (Jyoti, 2013;Yousef et al, 2014), job burn out (Dinibutun et al, 2020;Seyyedmoharrami et al, 2019). Whereas , an array of past and contemporary researchers have associated the organizational climate with turnover intentions such as Bracarense et al (2022) conducted in the health industry, a research indicated that organizational atmosphere predicted turnover intentions.…”
Section: Organizational Climate and Turn-over Intentionmentioning
confidence: 99%